2021
DOI: 10.3390/molecules26082115
|View full text |Cite
|
Sign up to set email alerts
|

A New Coumarin-Acridone Compound as a Fluorescence Probe for Fe3+ and Its Application in Living Cells and Zebrafish

Abstract: A new coumarin-acridone fluorescent probe S was designed and synthesized, and the structure was confirmed with 1H/13C NMR spectrometry, single-crystal X-ray diffraction, and high-resolution mass spectrometry. This probe has high sensitivity and selectivity for Fe3+ over other testing metal ions at 420 or 436 nm in acetonitrile–MOPS (3-Morpholinopropanesulfonic Acid) buffer solution (20.0 μM, pH = 6.9, 8:2 (v/v)). Under physiological conditions, the probe displayed satisfying time stability with a detection lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…As a small organic fluorophore containing several condensed nuclei in a fluorescent open form (see Figure 1 (b), the fulvate molecule produces intense violet (360 nm) and low-intensity green (560 nm) fluorescence at an excitation wavelength of 280 nm. The emission peaks in the short-and long-wavelength regions of the FL spectrum can be caused by excited state intramolecular proton transfer (ESIPT), which is characteristic of fragments with intramolecular hydrogen bonds [43]. Since the EHS solution demonstrated near-ultraviolet transparency and increased far-ultraviolet absorption in the absence of detectable analytical wavelengths (Figure 6 (c)), it is convenient to characterize the EHS structure by fluorescence spectra (Figure 6 (d)).…”
Section: Fluorescence (Fl) and Ultraviolet (Uv)-spectroscopymentioning
confidence: 99%
“…As a small organic fluorophore containing several condensed nuclei in a fluorescent open form (see Figure 1 (b), the fulvate molecule produces intense violet (360 nm) and low-intensity green (560 nm) fluorescence at an excitation wavelength of 280 nm. The emission peaks in the short-and long-wavelength regions of the FL spectrum can be caused by excited state intramolecular proton transfer (ESIPT), which is characteristic of fragments with intramolecular hydrogen bonds [43]. Since the EHS solution demonstrated near-ultraviolet transparency and increased far-ultraviolet absorption in the absence of detectable analytical wavelengths (Figure 6 (c)), it is convenient to characterize the EHS structure by fluorescence spectra (Figure 6 (d)).…”
Section: Fluorescence (Fl) and Ultraviolet (Uv)-spectroscopymentioning
confidence: 99%
“…[5][6][7][8] The human body requires about 30 mg per day to maintain a variety of life activities, [9] such as protein synthesis, osmotic pressure regulation, pH balance stability, hemoglobin formation, oxygen metabolism, cytochrome, enzyme catalysis, photocatalysis and electron transfer in DNA and RNA synthesis. [10][11][12][13][14][15][16][17] However, insufficient or excessive Fe 3 + content can lead to many health problems. [12,[14][15] Excessive Fe 3 + ion in the body may lead to the risk of osteoporosis, hemochromatosis, diabetes, depression, hepatitis, organ failure, respiratory problems, convulsions, cardiac arrest, ucleic acid and protein damage, gastrointestinal diseases and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[8,17,26,35] In contrast, fluorescent probe detection has the characteristics of high selectivity, high sensitivity, low cost, rapid response, visualization and biological imaging, which can make up for the shortcomings of traditional analytical methods. [11,[15][16]24,37] At present, there are many reports on fluorescence sensing for the detection of Fe 3 + , including organic small molecules, [4][5][6][11][12]16,18,20,26] metal organic frameworks [2,[7][8]10,38,[40][41][42] , quantum dots and so on. [9,[13][14][15]39,43] However, when considering the practical application ability of the probe in selectivity, sensitivity, competitiveness and applicable conditions, researchers believe that there is still a need for development and progress for Fe 3 + fluorescent sensors.…”
Section: Introductionmentioning
confidence: 99%
“…By studying the potential energy curves (PECs) along the NH coordinate, the authors concluded that the intramolecular PT (from NH indole to CO of the acridone) occurs at the excited state with a barrier of 6.7 kcal/mol. In another recent study, a coumarin‐acridone derivative had dual fluorescence, but the PT originated from an intermolecular hydrogen bond with a polar solvent molecule such as CH 3 COOH [71].…”
Section: Introductionmentioning
confidence: 99%